Cultivating religious moderation in early childhood: an innovative steam-based instructional design - Syarfina; Fakhrizal (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background: Religious moderation (RM) learning in early childhood education (ECE) is essential for fostering tolerance, peaceful attitudes, and balanced religious understanding from an early age; however, its classroom implementation remains limited. Objective: This study aims to develop an instructional design in the form of a STEAM-based teacher guidebook to support the integration of religious moderation values into early childhood learning. Method: Employing a Research and Development (R&D) approach using the 4D model (define, design, develop, and disseminate), the study involved ten early childhood education teachers in Langsa City, Indonesia. Data were collected through expert validation questionnaires covering media, content, and language aspects, as well as a practicality questionnaire administered to teachers as end users. Result: The results indicate that the developed guidebook achieved a feasibility score of 95% from media experts, 84.6% from content experts, and 97.5% from language experts. In addition, the practicality test yielded a score of 94.5%, indicating high usability for classroom implementation. The novelty of this study lies in the systematic development of a STEAM-based instructional guide that concretely integrates religious moderation values into thematic learning activities aligned with early childhood developmental stages, providing a practical solution for early childhood educators. Conclusion: These findings suggest that the developed STEAM-based instructional guidebook offers a practical and innovative pedagogical contribution to strengthening religious moderation and character education in early childhood settings